2018
DOI: 10.1186/s12889-018-6053-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with pre-diabetes and diabetes mellitus in Kenya: results from a national survey

Abstract: BackgroundDiabetes Mellitus is one of the four major non-communicable diseases causing about 4 million deaths in 2017. By 2040, low income countries are projected to experience 92% increase in mortality due to diabetes. Undiagnosed diabetes poses a public health concern with costly public health implications especially in Africa. It is therefore crucial to examine the burden and risk factors for diabetes at national level to inform policy and national programs.MethodsData from the 2015 Kenya national STEPs sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
78
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 45 publications
13
78
8
Order By: Relevance
“…Our results suggest that there is an undetected burden of diabetes in rural western Kenya, perhaps greater than the 2-3% estimated in the country-wide survey [19]. The burden of diabetes in the Kombewa HDSS is likely to be higher than what our data determined due to the number people who are not diagnosed and the growing population of people living with diabetes that were not examined in our study.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Our results suggest that there is an undetected burden of diabetes in rural western Kenya, perhaps greater than the 2-3% estimated in the country-wide survey [19]. The burden of diabetes in the Kombewa HDSS is likely to be higher than what our data determined due to the number people who are not diagnosed and the growing population of people living with diabetes that were not examined in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…The burden of diabetes in the Kombewa HDSS is likely to be higher than what our data determined due to the number people who are not diagnosed and the growing population of people living with diabetes that were not examined in our study. The national survey in Kenya show that > 50% of those testing positive for diabetes, via fasting blood glucose, in Kenya are unaware of their condition, making them unlikely to report this in a verbal autopsy interview [19].…”
Section: Discussionmentioning
confidence: 99%
“…The first nationally representative survey of 2015 found an age‐standardized DM prevalence of 2.4% with 3.1% of Kenya's population having impaired fasting glycemia . The increasing prevalence and the chronic nature of DM makes it a costly disease both to Kenya's health system and the affected households as it has been shown that persons with diabetes incur up to three times higher medical costs compared with nondiabetics .…”
Section: Introductionmentioning
confidence: 99%
“…The number of female participants (80, 51.6%) was more than males (75, 48.4%). In the study by Mohamed S. F. et al 10 it was found that majority of the participants 46.1% were in the age group of 18-29 followed by 32.7% in the age group 30-44 and then 15.9% in the age group 45-59 years of age. 66.1% of participants were either married or were living together, and about 51% were females.…”
Section: Discussionmentioning
confidence: 95%